Haploidentical transplantation in high‐risk pediatric leukemia: A retrospective comparative analysis on behalf of the Spanish working Group for bone marrow transplantation in children (GETMON) and the Spanish Grupo for hematopoietic transplantation (GETH). Issue 1 (5th November 2019) - Pérez‐Martínez, Antonio; Ferreras, Cristina; Pascual, Antonia; Gonzalez‐Vicent, Marta; Alonso, Laura; Badell, Isabel; Fernández Navarro, José María; Regueiro, Alexandra; Plaza, Mercedes; Pérez Hurtado, Jose María; Benito, Ana; Beléndez, Cristina; et al.
Abstract: A total of 192 pediatric patients, median age 8.6 years, with high‐risk hematological malignancies, underwent haploidentical stem cell transplantation (haplo‐HSCT) using post‐transplantation cyclophosphamide (PT‐Cy), or ex vivo T cell‐depleted (TCD) graft platforms, from January 1999 to December 2016 in 10 centers in Spain. Some 41 patients received an unmanipulated graft followed by PT‐Cy for graft‐vs‐host disease (GvHD) prophylaxis. A total of 151 patients were transplanted with CD3‐depleted peripheral blood stem cells (PBSCs) by either CD34 + selection, CD3 + CD19 + depletion, TCRαβ + CD19 + depletion or CD45RA + depletion, added to CD34 + selection for GvHD prophylaxis. The PBSCs were the only source in patients following ex vivo TCD haplo‐HSCT; bone marrow was the source in 9 of 41 patients following PT‐CY haplo‐HSCT. Engraftment was achieved in 91.3% of cases. A donor younger than 30 years, and the development of chronic GvHD were positive factors influencing survival, whereas positive minimal residual disease (MRD) before transplant and lymphoid disease were negative factors. The probability of relapse increased with lymphoid malignancies, a donor killer‐cell immunoglobulin‐like receptor (KIR) haplotype A and positive MRD pretransplant. No difference was found in overall survival, disease‐free survival or relapse incidence between the two platforms. Relapse is still of concern in both platforms, and it should be the focus of future efforts. In conclusion, both platforms for haplo‐HSCT were effective and could be utilized depending on the comfort level of the center.